Development of management model for the sports climbing association of Thailand - Sikawkhiew, Sutas (Edelweiss Applied Science and Technology, 2024)
This research aimed to 1) study the management components of the Sports Climbing Association of Thailand in Trang Province; 2) develop and verify a management model for the Sports Climbing Association of Thailand; and 3) evaluate the practicality and suitability of the management model for the Sports Climbing Association of Thailand using Delphi future research techniques. The research involved 5 experts participating in semi-structured interviews and 17 experts responding to surveys, with an additional 11 stakeholders selected with purposive sampling for focus group discussions. These participants included committee members, referees, coaches, and other stakeholders involved with the Sports Climbing Association of Thailand. The research tools used included semi-structured interviews and questionnaires, with data analyzed using median, mode, and interquartile range statistics. The findings revealed that the development of the management model for the Sports Climbing Association of Thailand consists of (1) 4 dimensions and 28 components of management; (2) 5 dimensions and 30 components for promoting development within the association, with unanimous agreement and consistent opinions among the qualified experts on all items; and (3) verification of the model’s practicality and suitability through focus group discussions, where expert opinions suggested additional improvements and consensus on practical implementation.